Development of objective-oriented components for ATM networks simulation with emphasis on switch architecture / Tan Boon Pin - Tan, Boon Pin (2001)
Asynchronous Transfer Mode (ATM) is considered to be the ground on which B-ISDN is to be built. It is the new generation of communication networks that are being deployed throughout the telecommunication industry. The basic functions of ATM switch are to direct cells from input port to output port and to buffer cell destined to the same output port from different input port. This project focuses on the development of an object-oriented simulator for simulation. The simulator is designed and implemented to ensure the correctness of routing within the switch fabric, fairness of switching and to guarantee quality of service for ATM applications. As such, the implemented switching architecture is based on the Banyan NxN technique. Finally, object-oriented approach will be used for the development of network simulator. The language I'll be using is Java and the tool is Borland JBuilder.